Metallothionein as a Scavenger of Free Radicals - New Cardioprotective Therapeutic Agent or Initiator of Tumor Chemoresistance? - Heger, Zbynek; Rodrigo, Miguel Angel Merlos; Krizkova, Sona; Ruttkay-Nedecky, Branislav; Zalewska, Marta; Del Pozo, Elena Maria Planells; Pelfrene, Aurelie; Pourrut, Bertrand; Stiborova, Marie; Eckschlager, Tomas; Emri, Gabriella; Kizek, Rene; et al. (Current drug targets, 2016)
Cardiotoxicity is a serious complication of anticancer therapy by anthracycline antibiotics. Except for intercalation into DNA/RNA structure, inhibition of DNA-topoisomerase and histone eviction from chromatin, the main mechanism of their action is iron-mediated formation of various forms of free radicals, which leads to irreversible damage to cancer cells. The most serious adverse effect of anthracyclines is, thus, cardiomyopathy leading to congestive heart failure, which is caused by the same mechanisms. Here, we briefly summarize the basic types of free radicals formed by anthracyclines and the main processes how to scavenge them. From these, the main attention is paid to metallothioneins. These low-molecular cysteine-rich proteins are introduced and their functions and properties are reviewed. Further, their role in detoxification of metals and drugs is discussed. Based on these beneficial roles, their use as a new therapeutic agent against oxidative stress and for cardioprotection is critically evaluated with respect to their ability to increase chemoresistance against some types of commonly used cytostatics.
Keywords: oxidační stres; Metallothionein; srdeční selhání; protinádorová antibiotika; Anthracyclines; Neoplasms; Cardiomyopathies; metalothionein; chemorezistence; kardiomyopatie; Cardiotonic Agents; Animals; lidé; Heart Failure; Humans; zvířata; Free Radicals; Antibiotics, Antineoplastic; Free Radical Scavengers; kardiotonika; antracykliny; nádory; Drug Resistance, Neoplasm; volné radikály; Oxidative Stress; scavengery volných radikálů